Rice Husk Ash for Fast Removal of 2,4-Dichlorophenoxyacetic Acid from Aqueous Solution - Sunil K. Deokar; Sachin A. Mandavgane (Adsorption Science & Technology)
Rice husk ash (RHA) is a rich source of micronutrients and improves yield, and is spread on agriculture lands as a farming practice. For the first time, RHA has been evaluated as an adsorbent for pesticide removal from aqueous solutions. RHA was characterized extensively by X-ray fluorescence, Fourier transform infrared spectroscopy, BET surface area, CO 2 , H 2 O, N 2 and SO 2 (CHNS) analysis. 2,4-Dichlorophenoxyacetic acid (2,4-D), a commonly used pesticide, was chosen as a representative adsorbate for studying the effects of various parameters in batch adsorption. Compared with granulated activated carbon, RHA gave 10,000 times higher rate constant. Thus, RHA adsorbs 2,4-D instantly and stops its further transport through soil. On the basis of adsorption capacity, RHA dosage per hectare of land is recommended for different crops and fruits. Thus, RHA serves dual purposes: (a) as a source of micronutrients and (b) as an effective adsorbent for fast removal of pesticide, in addition to inhibiting groundwater leaching.